حماية الأطفال اللاجئين بسبب حالات الطوارئ - محمد، محمد النذير الزين عبدالله (جامعة البحر الأحمر, 2016)
This study addresses the issue of "protection of children refugee because of emergencies," although there is no international law frames the legal provisions of the humanitarian protection of the rights of refugees, but there is no tight comprehensive international legal system that frames the protection of refugee children, and this is one of the main problems facing the international community to confront the phenomenon of asylum children and provide effective protection mechanisms and dedicated to it. The study follows inductive analytical comparative methodology. The study was concluded the most important results, which include: some countries are not cooperating with refugee issues, there is no special clear definition of a child refugee in the scope of the international conventions on refugees, There is no special international convention keeps and ensures the protection of children refugee. The most important recommendations of the study are: the international consensus for the development of child-specific refugee convention, plans and controls to deal with emergency situations causing asylum, the necessity of international solidarity in order to provide humanitarian assistance to refugee children, the necessity to take advantage of the rules of the Islamic jurisprudence that organize and developed asylum. The necessity to develop a strategic security for the refugee camps to fight the criminal actions
تهدف هذه الدراسة لتسليط الضوء على موضوع )حماية الأطفال اللاجئين بسبب حالات الطوارئ(، وعلى الرغم من أنه يوجد قانون دولي يؤطر لأحكام قانونية إنسانية لحماية حقوق اللاجئين، إلا أنه لا يوجد نظاماً قانونياً دولياً شاملاً ومحكماً يؤطر لحماية الأطفال اللاجئين وهذا من أهم المشكلات التي تواجه الأسرة الدولية لمجابهة ظاهرة لجوء الأطفال وتوفير آليات حماية فعالة ومخصصة لذلك.ختمت الدراسة بأهم النتائج والتي شملت: بعض الدول باتت لا تتعاون مع قضايا اللاجئين، أنه لا يوجد تعريف خاص ومحكم للطفل اللاجئ في نطاق الاتفاقيات الدولية المعنية باللاجئين، لا توجد اتفاقية دولية خاصة تصون وتضمن حماية الأطفال اللاجئين.ثم جاءت توصيات الدراسة والتي من أهمها: ضرورة التوافق الدولي لوضع اتفاقية خاصة بالطفل اللاجئ، وضع خطط وضوابط للتعامل مع حالات الطوارئ المسببة للجوء، ضرورة التضامن الدولي من أجل تقديم المساعدات الإنسانية للأطفال اللاجئين، ضرورة الاستفادة من قواعد الفقه الإسلامية المنظمة للجوء وتطويرها. ضرورة وضع استراتيجية أمنية لمخيمات اللاجئين لمحاربة العمليات الإجرامية فيها.
Keywords: حقوق الإنسان -- اللاجئين -- حقوق اللاجئين -- الأطفال اللاجئين -- حالة الطوارئ -- القانون السودانى -- القانون الدولى الإنسانى